PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBASIS PENDEKATAN SAINTIFIK MATERI GETARAN GELOMBANG SISWA KELAS VIII SMP ISLAM PLUS JABAL NOOR - Gustapu, Tri Adi; Laili, Alik Mustafidal (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The science learning process at SMP Islam Plus Jabal Noor, especially in class VIIIA on vibration and wave material, has so far still used simple media in the learning process and the methods applied, such as lectures and discussions, so that students feel bored and tired in understanding the material. This study aims to develop learning media in the form of animated videos based on a scientific approach to the material of wave vibrations and to determine the level of validity and practicality based on the assessment of media experts and material experts and teacher and student response questionnaires. This study uses the Research and Development (R&D) research method adapted from the ADDIE development model. The results of this study indicate that the level of validity of animated video learning media based on a scientific approach to the material of wave vibrations for class VIII students of SMP Islam Plus Jabal Noor based on the assessment of media experts from both validators is 83.33% with the criteria